Avaliação do programa de despoluição da Baía de Guanabara e do programa nova baixada para o saneamento básico na Baixada Fluminense - Santos Neto, Guilherme Malaquias dos (2002)
In this dissertation we examine the basic sanitation po(icy of Rio de Janeiro State, based on a study comparing two govemmont projects: the Nova Baixada Program - NBP and the Guanabara Bay Cleanup Program - GBCP, which are two of the major projects promoted by the State. The analysis aims at establishing the relationship between programs with an environmental impact and programs with a social impact. The focus of this study is on the social benefits accessible to the low-income popuiation of the counties where the programs are beng simultaneously implemented. The study also examines the management aspect, by assessing how political and operational issues can influence the expected results.